The FATIGUE-PRO: a new patient-reported outcome instrument to quantify fatigue in patients affected by systemic lupus erythematosus. (13th December 2021) - Morel, Thomas; Cano, Stefan; Bartlett, Susan J; Gordon, Caroline; Haier, Birgit; Regnault, Antoine; Schneider, Matthias; Stach, Christian; Cleanthous, Sophie
Abstract: Objectives: This study aimed to implement a patient-centred and evidence-based approach to develop a novel patient-reported outcome (PRO) instrument to measure fatigue in patients with SLE. Methods: A three-step mixed methods psychometric (MMP) approach was followed. Steps comprised first draft item generation and review using interview data; evaluation and refinement of second draft items using mixed methods data, including interview and quantitative data from a phase 2 clinical study in SLE analysed using Rasch Measurement Theory (RMT) analysis; and evaluation of the final FATIGUE-PRO items using RMT and complementary Classical Test Theory (CTT) analyses. Guided by MMP criteria, a team of clinicians and outcome-measurement experts assessed evidence to inform instrument development. Results: Step 1 culminated in 55 items ( n = 39 patients interviewed). Their refinement in step 2 using mixed methods evidence led to the final FATIGUE-PRO instrument comprising 31 items across three scales of fatigue: physical fatigue (9 items), mental and cognitive fatigue (11 items) and susceptibility to fatigue (11 items). Qualitative ( n = 43 patients) and quantitative ( n = 106 patients) evidence strongly supported the scales' content comprehensiveness and targeting, item quality and fit, conceptual uniqueness and appropriateness of the response scale. The FATIGUE-PRO further benefited from excellent reliability (RMT: 0.92–0.94 and CTT: 0.95–0.96) and supportive evidence of construct validity from assessments against other PROs. Conclusion: The conceptual advances, comprehensive coverage and strong psychometric properties of the FATIGUE-PRO will significantly advance the measurement and management of fatigue in SLE, both in clinical trials and routine practice. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov ), NCT02804763